Decoding Schemes for FBMC with Single-Delay STTC. (26th January 2010) - Lélé Lélé, Chrislin Chrislin; Le Ruyet Le Ruyet, Didier Didier
Abstract : Orthogonally multiplexed Quadrature Amplitude Modulation (OQAM) with Filter-Bank-based MultiCarrier modulation (FBMC) is a multicarrier modulation scheme that can be considered an alternative to the conventional orthogonal frequency division multiplexing (OFDM) with cyclic prefix (CP) for transmission over multipath fading channels. However, as OQAM-based FBMC is based on real orthogonality, transmission over a complex-valued channel makes the decoding process more challenging compared to CP-OFDM case. Moreover, if we apply Multiple Input Multiple Output (MIMO) techniques to OQAM-based FBMC, the decoding schemes are different from the ones used in CP-OFDM. In this paper, we consider the combination of OQAM-based FBMC with single-delay Space-Time Trellis Coding (STTC). We extend the decoding process presented earlier in the case of N t = 2 transmit antennas to greater values of N t . Then, for N t ≥ 2, we make an analysis of the theoretical and simulation performance of ML and Viterbi decoding. Finally, to improve the performance of this method, we suggest an iterative decoding method. We show that the OQAM-based FBMC iterative decoding scheme can slightly outperform CP-OFDM.